2007
DOI: 10.1111/j.1365-2214.2007.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Incredible Years Basic parent training programme as an early intervention for children with conduct problems and ADHD

Abstract: Findings from this study indicate that the IY PT programme is a valuable intervention for many pre-school children displaying early signs of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 35 publications
6
153
0
8
Order By: Relevance
“…Consistent with this picture a recent study in a Dutch sample found effects of generic parent training on both internalizing and general behavior problems but not ADHD symptoms [37]. Where studies have shown positive effects of parent training on ADHD symptoms these have typically included children who have general patterns of disruptive behavior disorders including children with raised levels of ADHD symptoms, but who do not have a rigorous diagnosis of ADHD [17]. One reason why such approaches may not be optimal with regard to ADHD as a treatment target is that they are based on generic approaches designed to reduce difficult behaviors which are adapted to for ADHD populations [9] rather than being developed specifically to target ADHD behaviors or the psychological deficits thought to underlie them (e.g., executive dysfunction; [31]).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Consistent with this picture a recent study in a Dutch sample found effects of generic parent training on both internalizing and general behavior problems but not ADHD symptoms [37]. Where studies have shown positive effects of parent training on ADHD symptoms these have typically included children who have general patterns of disruptive behavior disorders including children with raised levels of ADHD symptoms, but who do not have a rigorous diagnosis of ADHD [17]. One reason why such approaches may not be optimal with regard to ADHD as a treatment target is that they are based on generic approaches designed to reduce difficult behaviors which are adapted to for ADHD populations [9] rather than being developed specifically to target ADHD behaviors or the psychological deficits thought to underlie them (e.g., executive dysfunction; [31]).…”
Section: Introductionmentioning
confidence: 80%
“…The value of such approaches for the treatment of oppositional behavior is confirmed by trials of parent training interventions developed for noncompliant children based on generic behavior modification principles such as Incredible Years [39] and Triple P [21]. These have also been shown to be effective in reducing oppositional behavior in ADHD children [2,17]. Consistent with this picture a recent study in a Dutch sample found effects of generic parent training on both internalizing and general behavior problems but not ADHD symptoms [37].…”
Section: Introductionmentioning
confidence: 99%
“…All eleven [13][14][15][16][17][18][19][20][21][22][23] studies had a child ADHD symptom outcome (assessed using clinical interview or validated parental reported questionnaire). The overall standardized mean difference in the analysis for ADHD symptoms was significant and moderate (SMD = 0.68; 95%…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when the diagnoses were validated against the CBCL and TRF attention subscales, it turned out that the group reported to have the diagnosis also scored significantly higher on both parent and teacher ratings of attention problems. These subscales include several items similar to those that define ADHD in the DSM-IV manual (American Psychiatric Association [APA], 1994) and in previous studies concepts like ADHD-related behavior (Thapar, Harrington, & McGuffin, 2001) and symptoms of ADHD (Jones, Daley, Hutchings, Bywater, & Eames, 2007) have been used with children with high scores on these types of scales.…”
Section: Discussionmentioning
confidence: 99%